2002
DOI: 10.1006/jjie.2001.0491
|View full text |Cite
|
Sign up to set email alerts
|

The Location of Japanese Investments in China: Agglomeration Effects, Keiretsu, and Firm Heterogeneity

Abstract: Conditional logit analysis of the locational choice by Japanese electronics firms in China's regions and provinces during 1990-1995 confirms a major impact of general industry, Japanese, and keiretsu-specific agglomeration benefits. Further analysis reveals a substantial aggregation bias due to the presence of firm heterogeneities in terms of investor size and market orientation of manufacturing investments. Small and medium sized enterprises are more sensitive to distance from Japan and Japanese agglomeration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
148
2
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(169 citation statements)
references
References 26 publications
10
148
2
3
Order By: Relevance
“…In their study about the FDI location decision of Japanese investments in China, Belderbos and Carree (2002) found that there is a difference in the locational investment criteria between Japanese small and medium-sized companies (SMEs) and MNEs. Unlike Japanese MNEs, Japanese SMEs tend to cluster next to the other Japanese companies and geographically closer to their headquarters in Japan.…”
Section: Fdi Location Choice Factors At the Regional Levelmentioning
confidence: 99%
“…In their study about the FDI location decision of Japanese investments in China, Belderbos and Carree (2002) found that there is a difference in the locational investment criteria between Japanese small and medium-sized companies (SMEs) and MNEs. Unlike Japanese MNEs, Japanese SMEs tend to cluster next to the other Japanese companies and geographically closer to their headquarters in Japan.…”
Section: Fdi Location Choice Factors At the Regional Levelmentioning
confidence: 99%
“…Empirical studies have confirmed that MNEs are more likely to locate plants in large (regional) markets (e.g. Head et al, 1995;Mayer and Muchielli, 1999) and regions with lower labour cost (Belderbos and Carree, 2002;Mayer and Muchielli, 1999;Wheeler and Mody, 1992). As market demand and labour costs are the environmental changes that are most influential in attracting investments, changes in market demand and labour costs are also likely to lead MNEs to extend or reduce operations of existing affiliates.…”
Section: Hypothesesmentioning
confidence: 99%
“…A large number of studies have examined the firm-level determinants of the decision to become a MNE (e.g. Belderbos and Sleuwaegen, 1996;Kogut and Chang, 1991;, the choice of entry mode abroad (Delios and Beamish, 1999b;Hennart, 1991;Barkema and Vermeulen, 1998), and the location choice for new affiliates (Head et al, 1995;Shaver and Flyer, 2000;Chung and Alcacer, 2001;Belderbos and Carree, 2002). Other studies have examined the impact of multinational expansion and geographic scope on overall firm performance (Delios and Beamish, 1999a;Hitt et al, 1997;Tallman and Li, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…High labor costs has been found to be a deterrent to FDI in some studies (Belderbos & Carree, 2002;Cheng & Kwan, 2000;Fung et al, 2002;Wei & Liu, 2001;Li et al, 2008). However, Baghwati and Srinivasan (1983), Coughlin et al (1991) and Wang and Swain (1995) in their respective studies found a correlation between wage and labor cost.…”
Section: The Determinants Of Location Choicementioning
confidence: 97%